2014
DOI: 10.1039/c4tc00826j
|View full text |Cite
|
Sign up to set email alerts
|

Size controlled synthesis of carbon quantum dots using hydride reducing agents

Abstract: Highly luminescent carbon quantum dots (CQDs) are synthesized at room temperature by hydride reduction of carbon tetrachloride (CCl4) within inverse micelles. Regulation of the average diameter of the allylamine terminated CQDs is achieved by varying the strength of the reducing agent used. Transmission electron microscopy shows that the NCs are highly crystalline with well-defined core diameters tuned from 2 to 6 nm, while FTIR and XPS spectroscopy confirm that the CQDs possess similar surface chemistry. UV-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…Similar observations have been detected in the reduction of α,β‐unsaturated ketones,17 β‐substituted ketones,18 enamines,19 imines,20,21 and anhydrides 22. The steric bulk of a reducing fragment has even been shown to play a factor in the size distribution of quantum dots 23. In transition metal chemistry, steric bulk is often quantified by the measure of a ligand’s cone angle, or bite angle,24,25 but the values determined refer to the size of a ligand, and do not give much insight into the size of the transition metal fragment towards its interaction with the substrate.…”
Section: Introductionsupporting
confidence: 69%
“…Similar observations have been detected in the reduction of α,β‐unsaturated ketones,17 β‐substituted ketones,18 enamines,19 imines,20,21 and anhydrides 22. The steric bulk of a reducing fragment has even been shown to play a factor in the size distribution of quantum dots 23. In transition metal chemistry, steric bulk is often quantified by the measure of a ligand’s cone angle, or bite angle,24,25 but the values determined refer to the size of a ligand, and do not give much insight into the size of the transition metal fragment towards its interaction with the substrate.…”
Section: Introductionsupporting
confidence: 69%
“…Spherical γ-Fe 2 O 3 /NCDs with sizes in the range of ∼9 ± 3 nm were observed in the high-resolution TEM (HRTEM) image ( Figure 3 c), which is close to the typical size range of pristine CDs, indicating that the γ-Fe 2 O 3 dopant has a rather small effect in terms of the size and the shape of the nanoparticles. The selected area electron diffraction (SAED, Figure 3 d) reveals the phases of both NCDs (200) 22 , 23 and γ-Fe 2 O 3 (311, 400). 24 , 25 The size distribution of γ-Fe 2 O 3 /NCD particles was assessed also by DLS measurements, which showed that the main population was within the size range of 12–20 nm with a peak corresponding to 14 nm, which is in a good agreement with the TEM observation (Figure S1, see the Supporting Information ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The methods such as laser ablation, 23-25 electrochemical 26,27 and high energy ball milling 28 are categorized under the top-down methods for synthesis of CQDs. The bottom-up methods for synthesizing of CQDs which means synthesis from small molecules or carbonization, include hydrothermal, 29-31 solvothermal, 32,33 combustion, 34 pyrolysis, 35 microwave-assisted synthesis, 36-41 ultrasonic, [42][43][44] reverse micelles, 45,46 chemical vapor deposition (CVD), 47 and etc. Table 2 summarizes different synthesis methods of CQDs from versatile precursors, their optical properties, and their applications.…”
Section: Synthesismentioning
confidence: 99%